Innovative Pedagogy: A Case Study – the Culinary Arts College in Taiwan - HSIA, Hui-Wen; HO, Sophia Shi-Huei; CHEN, Robin Jung-Cheng (International Dialogues on Education Journal, 2017)
Lifelong learning has been recognized by many internationally renowned organizations which claim that people should possess certain life skills or competences to live in a world full of complex uncertainties. In this study, we propose A phaslised, thematic and socialised (PTS) pedagogy as a teaching approach to address the issues concerning how to equip learners with better capabilities. The qualitative method was employed based on a case study where interviews with several stakeholders were conducted. Observation of PTS practice and analysis of school documents were also carried out. The findings revealed that this strategy emphasizes a learner-oriented path, the development of their problem-solving ability and the culture of mutual partnership and intensive cooperation in the teacher community. Despite of several merits originating from PTS pedagogy, there remain a few issues to address, including the challenges to teachers in practising this approach, the appropriate means to evaluate students’ learning outcomes and the degree of autonomy granted to the students.